Higher Values in Bangka Belitung Folklore and Its Contemporer Context - Asyraf Suryadin; Tien Rostini; Diana Anggraeni; Nanda Saputra (Britain International for Academic Research (BIAR-Publisher), 2022)
This research finds out how far the noble values are contained in the Bangka Belitung folklores. These values are the result of the human mind reflection which will indirectly be revealed in folklore. Through the analysis of the noble value's description of each folklore, then it is simply sorted and observed which values are the most prominent. Qualitatively, there are 28 types of noble values with a total of 103 occurrences of noble values from the combination of the five Bangka Belitung folklores. The more dominant noble values are 20 social values, 11 hard work values, 10 compassion values, religious values, 8 culture and caring values. As for honesty and tenacity, they have 4 values. The noble values contained in the Bangka Folklore is relevant in the current state of individualism. The spirit of social care, hard work, compassion, and religious values persists in rural communities in Bangka Belitung.